Transformative Learning on Social Studies: Case Study of the Independence Meaning for Students - Maskur, Rini; Suprijono, Agus; Jacky, M. (IKIP Widya Darma Surabaya, 2024)
Objective: This study aimed to analyze the implementation of transformative learning as an alternative learning model to improve the students’ perception about the meaning of independence, as the learning material for the sixth grade students in elementary school. Method: The research utilized a qualitative approach, with data collection methods include surveys, interviews, and focus group discussions. The analysis revealed that students through the transformative learning in action rearch can come out and relate their minds about the meaning of being free, the meaning of independence in general, and lasted to their awareness about how hard was the warriors’ struggled to reach the Indonesian’s independence. Keywords such as transformative learning, meaning of independence, elementary school, social studies, and case study. Results: One of the results of this research was that at last the sixth grades students of Magersari Elementary public school can join the flag ceremony every Monday morning peacefully and seriously, because it was one of their efforts to respect the struggled of the heroes. Last, the sixth grades students could be a good role model for the younger students. Novelty: By analyze the implementation of Transformative learning on social studies as a Case study of the independence meaning for students which has never been researched using the latest year’s data, the researcher expects this article can bring novelty and useful for elementary education.